Register Expansion and SemaCall: 2 low-overhead dynamic Watermarks suitable for Automation in LLVM [Source code and Raw Experiment data] - Schwarzbeck, David; Schuh, Jan; Hammrich, Mercel; Philippsen, Michael; Novac, Daniela (2024)
This archive contains the source code for both presented watermarks and the test-suite with the raw data from the experiments of the conference paper "Register Expansion and SemaCall: 2 low-overhead dynamic Watermarks suitable for Automation in LLVM" published In Proc. 2024 Workshop on Research on Offensive and Defensive Techniques in the Context of Man At The End Attacks (CheckMATE’24)., Salt Lake City, U.S.
Keywords: Software Watermarks; Dynamic; LLVM; Anti Piracy